Assessment of delta-9-tetrahydrocannabinol (THC) in saliva and blood after oral administration of medical cannabis with respect to its effect on driving abilities - Trojan, Václav; Landa, Leoš; Hřib, Radovan; Jurica, Jan; Rychlíčková, Jitka; Zvoníček, Václav; Halamkova, Lenka; Halamek, Jan; Demlová, Regina; Belaskova, Silvie; Slíva, Jiří (Physiological research, 2022)
Medical cannabis has recently been legalized in many countries, and it is currently prescribed with increasing frequency, particularly for treatment of chronic pain resistant to conventional therapy. The psychoactive substance delta-9-tetrahydro-cannabinol (THC) contained in cannabis may affect driving abilities. Therefore, the aims of this study (open-label, monocentric, nonrandomized) were to evaluate blood and saliva concentrations of THC after oral administration of medical cannabis and to assess the time needed for THC levels to decline below a value ensuring legal driving. The study involved 20 patients with documented chronic pain using long-term medical cannabis therapy. They were divided into two groups and treated with two different doses of cannabis in the form of gelatin capsules (62.5 mg or 125 mg). In all patients, the amount of THC was assessed in saliva and in blood at pre-defined time intervals before and after administration. THC levels in saliva were detected at zero in all subjects following administration of both doses at all-time intervals after administration. Assessment of THC levels in blood, however, showed positive findings in one subject 9 h after administration of the lower dose and in one patient who had been given a higher dose 7 h after administration. Our finding suggested that for an unaffected ability to drive, at least 9-10 h should elapse from the last cannabis use.
Keywords: sliny; Saliva; Cannabis; tetrahydrokanabinol; agonisté kanabinoidních receptorů; aplikace orální; marihuana pro léčebné účely; Humans; Chronic Pain; Dronabinol; Administration, Oral; lidé; Cannabinoid Receptor Agonists; Medical Marijuana; chronická bolest